Joint and sternal cracking in physically active individuals – clinical significance and current evidence - Głąb, Łukasz; Płusa, Aleksandra; Broda, Damian; Komissarova, Daria; Ciesielska, Izabela; Janczylik, Paulina; Toczek, Martyna; Ryszka, Paulina; Cyls, Dawid; Broda, Aleksandra (Journal of Education, Health and Sport, 2026)
Introduction and purpose Joint cracking and audible sounds perceived in the sternum or anterior chest wall are common in physically active individuals. Although isolated sounds without red flags are usually physiological, anterior chest symptoms frequently raise concern because they may be misinterpreted as cardiopulmonary. This narrative review summarizes current evidence on mechanisms and clinical relevance of joint and sternal/chest wall cracking in active populations. State of knowledge Evidence from biomechanical and clinical literature suggests that sternal/chest wall cracking most often reflects musculoskeletal causes—sternoclavicular joint dysfunction, costosternal/costochondral involvement, or slipping rib syndrome—and may also occur with overload or stress-related injury. Parallel research in synovial joints, particularly the knee, shows that acoustic emission (AE) and vibroarthrography (VAG) features correlate with joint function and can support machine-learning discrimination between healthy and pathological states; however, heterogeneity of sensors, tasks, and signal-processing pipelines limits comparability and clinical translation. Conclusions In the absence of pain, swelling, instability, functional limitation, or systemic symptoms, joint sounds alone should not be considered pathological. For sternal/anterior chest wall cracking, assessment should prioritize exclusion of urgent cardiopulmonary causes, evaluation of training load/technique, and targeted examination of the sternoclavicular joint and rib–sternum complex, with imaging when indicated. AE/VAG approaches are promising adjuncts for research and longitudinal monitoring, but routine clinical use requires standardized protocols and prospective validation.